Activism in the Academic Context: Navigating Scholarship, Social Justice, and Institutional Constraints - Matos, Tiago (International Higher Education, 2025)
<h3 id="this-paper-examines-the-tensions-between-academic-scholarship-and-activism-exploring-whether-scholars-have-a-moral-obligation-to-engage-with-social-justice-or-should-maintain-traditional-scholarly-detachment-it-analyzes-activisms-definition-within-academia-ethical-considerations-and-institutional-constraints-that-shape-public-engagement-as-universities-evolve-under-neoliberal-pressures-and-increasing-polarization-the-paper-interrogates-whether-activism-enhances-or-undermines-academic-missions-offering-a-framework-for-scholars-navigating-their-dual-roles-as-knowledge-producers-and-public-citizens" data-pm-slice="1 1 []">This article examines the tensions between academic scholarship and activism, exploring whether scholars have a moral obligation to engage with social justice or should maintain traditional scholarly detachment. It analyzes activism’s definition within academia, ethical considerations, and institutional constraints that shape public engagement. As universities evolve under neoliberal pressures and increasing polarization, the paper interrogates whether activism enhances or undermines academic missions, offering a framework for scholars navigating their dual roles as knowledge producers and public citizens.